The Fourth Person of the Trinity. The Phantasmatic Flesh of Christ and the Extra-Ontological Dehiscence - Prósperi, Germán Osvaldo (Revista de Filosofía, 2020)
The aim of this paper is to analyse, from a logical and ontological perspective, the concept of a fourth person in the Trinity, as it is presented by John of Damascus in De fide orthodoxa and De imaginibus. We argue that this fourth person challenges the logic of the trinitarian theology. Since the fourth person is irreducible to the divine or the human, or to the matter and the spirit, its nature falls beyond the ontology. Consequently, an extra-grammar fourth person, one beyond syntax, is required to verbalise it.